Une analyse économétrique de l’ajustement récent de la balance commerciale canadienne (1978-1979) - Dion, Richard; Létourneau, Raynald (L'Actualité économique, 1980)
AbstractThe Canadian merchandise trade surplus increased rather modestly in 1978 and 1979 given that the depreciation of the real exchange rate since 1977 had considerably reinforced our competitive position. With the aid of an econometric model, we try to measure the respective contributions of the factors influencing the merchandise trade balance during that period.Our partial equilibrium simulations reveal that the depreciation of the Canadian dollar, both in nominal and real terms, substantially improved the merchandise trade surplus. High capacity utilization rates in Canada had a substantial impact on the trade balance through a large increase of imports, especially imports of producers' equipment, and through a significant reduction of exports of manufactured goods other than automotive products.Excluding the automobile sector, which has experienced a "structural" change in the United States, cyclical divergences between the two countries did not influence substantially the evolution of the merchandise trade account over that period. The rapid improvement of the terms of trade in 1979 strongly contributed to the increase of the nominal merchandise trade surplus. Our simulations show that the rise in the prices of certain primary commodities relative to the U.S. prices of manufactured goods was an important factor behind the stronger terms of trade.